Does audit committee matter? Evidence from Tanzanian listed firms - Bernard Mnzava (The Central European Review of Economics and Management (CEREM), 2023)
Aim: The primary role of audit committees is to provide oversight in the financial reporting, audit process, internal controls and in compliance with regulations and laws. The objective of this paper is to investigate the impact of board audit committees attributes on firm performance. Design/Research methods: Using a sample of firms publicly traded on the Dar es Salaam Stock Exchange (DSE) during 1998-2018; this paper estimated fixed effects regressions to tests the hypotheses developed. Conclusions/findings: The results show that audit committee attributes are positively linked with firm financial performance. Specifically, the findings reveal that audit committee attributes as measured by audit committee meetings, existence of audit committees, audit committee size and audit committee independence have positive impact on corporate performance as measured by return on sales (ROS) and profitability. These findings confirmed that firms having audit committees performed better than those without audit committees. Originality/value of the article: There is scarce research which examines the link between audit committees and firm performance in developing countries. To date, there is no study that has investigated the relationship between audit committee characteristics and firm performance in Tanzania. This paper provides new evidence on the relationship between audit committee attributes and firm performance in Tanzanian environment. Implications of the research: Overall, the findings recommend existence of large independent audit committees which conducts their meetings regularly as it is ideally enhances firm financial performance.
Keywords: G3; N27; 330; Audit committee attributes; corporate governance; firm performance; Tanzania